Pandemic influenza A(H1N1pdm09) vaccine induced high levels of influenza-specific IgG and IgM antibodies as analyzed by enzyme immunoassay and dual-mode multiplex microarray immunoassay methods. Issue 8 (18th February 2020) - Kazakova, Anna; Kakkola, Laura; Ziegler, Thedi; Syrjänen, Ritva; Päkkilä, Henna; Waris, Matti; Soukka, Tero; Julkunen, Ilkka
Abstract: Influenza A viruses continue to circulate throughout the world as yearly epidemics or occasional pandemics. Influenza infections can be prevented by seasonal multivalent or monovalent pandemic vaccines. In the present study, we describe a novel multiplex microarray immunoassay (MAIA) for simultaneous measurement of virus-specific IgG and IgM antibodies using Pandemrix-vaccinated adult sera collected at day 0 and 28 and 180 days after vaccination as the study material. MAIA showed excellent correlation with a conventional enzyme immunoassay (EIA) in both IgG and IgM anti-influenza A antibodies and good correlation with hemagglutination inhibition (HI) test. Pandemrix vaccine induced 5–30 fold increases in anti-H1N1pdm09 influenza antibodies as measured by HI, EIA or MAIA. A clear increase in virus-specific IgG antibodies was found in 93–97% of vaccinees by MAIA and EIA. Virus-specific IgM antibodies were found in 90–92% of vaccinees by MAIA and EIA, respectively and IgM antibodies persisted for up to 6 months after vaccination in 55–62% of the vaccinees. Pandemic influenza vaccine induced strong anti-influenza A IgG and IgM responses that persisted several months after vaccination. MAIA was demonstrated to be an excellent method for simultaneous measurement of antiviral IgG and IgM antibodies against multiple virus antigens. Thus the method is well suitable for large scale epidemiological and vaccine immunity studies.